2017
DOI: 10.1016/j.ecolecon.2017.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Epistemology of Corporate Sustainability

Abstract: Business research is placing increasing focus on the relationship between the natural environment and the political concept of sustainable development. Within this nexus, one area, labelled 'Corporate Sustainability', emphasizes the interactions between economic, environmental and social values. The need to consider multiple values has contributed to a blur in the conceptual landscape. This is partly due to the fact that authors often address epistemological challenges on an implicit level. Moreover, hidden id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 40 publications
0
31
0
5
Order By: Relevance
“…The time factor and the acting dynamic are essential for this planning to have the desired effect both in the systemic and organizational level [61]. Searching for short-term results presents negative results for firms and managers that do so [55].…”
Section: Sustainability Practices-economic Categorymentioning
confidence: 99%
“…The time factor and the acting dynamic are essential for this planning to have the desired effect both in the systemic and organizational level [61]. Searching for short-term results presents negative results for firms and managers that do so [55].…”
Section: Sustainability Practices-economic Categorymentioning
confidence: 99%
“…For instance, Perez‐Batres, Doh, Miller, and Pisani () stated that strategic resources contribute to sustainability decisions while implementation is considered, and revealed priority conservation practices with cost savings with points, energy preservation and waste deduction as domains that are most likely to contribute to cost savings, resource conservation and water management. Current debates have concentrated on the concept of sustainability, but only for the business context, reflecting on how firms can provide development that recognizes the needs of future generations through assuring social standards and protecting the natural environment (Tseng et al, ; Vildåsen et al, ; Witjes et al, ) . In a recent study, Tseng et al () concluded that firms' capabilities in their supply chain networks must address multi‐aspects (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hemingway and Maclagan () presented a dilemma of inter‐subjective and knowledge attributes in the decision‐making process. For instance, Vildåsen, Keitsch, and Fet () debated in‐between economics and a systemic environmental aspect because the topic addresses balancing the creation of economic value with the environment and social concerns. Witjes, Vermeulen, and Cramer () noted that although firms have shown an increasing awareness of CS, integrating TBL into their business activities is still problematic.…”
Section: Introductionmentioning
confidence: 99%
“…At a fundamental level, the methodological approach resonates with the pluralist epistemology asserted by Vildåsen, Keitsch, and Fet (2017). A pluralistic setting implies that actors other than trained scholars can provide valid contribution to a knowledge debate, because real-world complexities of social and environmental concerns require collaboration between different actors, for example, academics and practitioners, to jointly define relevant problems (Schaltegger, Beckmann, & Hansen, 2013) and cocreate solutions (Arnold, 2017).…”
Section: About the Case Studymentioning
confidence: 99%